Creativity of Nanofiber Materials and Application in the Expressive Power of Manual Tie-Dyeing Process - Jing Wen; Xueqing Lu; Mai Jiang; Xiaohua Shao (Advances in Materials Science and Engineering)
Traditional printing and tie-dyeing are an important part of Chinese handicrafts. It consists of three main techniques: batik, tie-dye, and multi-layer dyeing. Among the traditional printing and dyeing techniques, tie-dyeing creates an ever-changing visual artistic effect due to the diversity of its production methods. In modern society with the unprecedented development of technology and information, people’s life rhythm has accelerated, and the opposite “slow fashion” has become popular. More and more people are focusing more on the traditional craft of tie-dyeing. In contemporary fiber art, raw materials have become the soul and foundation of fiber art. This is also the difference between modern fiber art and traditional textile art. Entering the new era, the demand for textiles by people of all countries is also increasing, new functional requirements are put forward for textiles, and functional textiles emerge as the times require. The creative display of nanofibers is a comprehensive grasp of the properties of the fibrous material. It is the creativity and expression generated under the premise of understanding the type, shape, craft, and expression of fiber. It fully reflects the characteristics of the material itself, and it is also the designer’s ideological expression of the texture and shape of the material. It is then materialized into a certain connotation by appropriate technical means. In this paper, manual tie-dyeing is applied to nanofiber materials, making full use of the advantages of modern nanomaterials to promote the development of fabric tie-dyeing technology. In the performance test of the transmittance of nanomaterials to ultraviolet rays, it can be found that the transmittance of nanomaterials through the tie-dyeing process is lower for optical fibers with shorter wavelengths. When the wavelength of ultraviolet light is 313 nm, the transmittance of ZnO to ultraviolet light is 0. When the ultraviolet wavelength is 435 nm, the transmittance of ZnO to ultraviolet light is 45%.